2017
DOI: 10.1038/srep42465
|View full text |Cite|
|
Sign up to set email alerts
|

pH-sensitive micelles for the intracellular co-delivery of curcumin and Pluronic L61 unimers for synergistic reversal effect of multidrug resistance

Abstract: Pluronic L61 unimers, which are biomacromolecular modulators, and curcumin, a small-molecule modulator, were co-formulated into pH-sensitive micelles to reveal the full synergistic potential of combination drug treatments to reverse multidrug resistance (MDR). Compared to monotherapy, combined therapy significantly improved the cytotoxicity, cellular uptake and apoptotic effects of doxorubicin (DOX) against MCF-7/ADR cells. In mechanistic studies, both L61 and curcumin enhanced the cytotoxic effect by acting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…The MMP of A2780/PTX cells treated by various PTX formulations was determined using JC-1, which undergoes a reversible transformation from a monomer (green florescence) into an aggregate form (red florescence) when it binds to a membrane with a high MP [ 27 ]. Mitochondrial depolarization (non-functional mitochondria) was indicated by a decrease in the ratio of the red/green fluorescence intensity.…”
Section: Results and Disussionmentioning
confidence: 99%
“…The MMP of A2780/PTX cells treated by various PTX formulations was determined using JC-1, which undergoes a reversible transformation from a monomer (green florescence) into an aggregate form (red florescence) when it binds to a membrane with a high MP [ 27 ]. Mitochondrial depolarization (non-functional mitochondria) was indicated by a decrease in the ratio of the red/green fluorescence intensity.…”
Section: Results and Disussionmentioning
confidence: 99%
“…Pluronic® F-127 (NP) polymer nanoparticles were fabricated using thin-lm hydration [46] and HA conjugated by the introduction of a disulphide pyridyl moiety (SAHA-NP-S-S) followed by HA-thiol treatment to obtain HA-coated F127 NPs (NP-HA) forming a disulphide linkage. SAHA payloads were incorporated into the micelles by co-dissolution prior to thin-lm formation.…”
Section: Physicochemical Characterisation Of Saha Pluronic F-127 Nanomentioning
confidence: 99%
“…Pluronic® F-127 is a water soluble, triblock copolymer consisting of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) repeats (PEO101-PPO56-PEO101) that possess a low toxicity in vivo, and is FDA approved [41]. F127 nanoparticles have been developed for the controlled release of therapeutic drugs, peptides and proteins [42][43][44] and with carboxylic groups to mediate the addition of tumour targeting moieties such a folate [45,46]. An alternative targeting moiety, HA is a naturally occurring glycosaminoglycan that consists of Nacetyl-d-glucosamine and d-glucuronic acid repeat units and is a ligand for the CD44 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Although conventional chemotherapy (CHT) performed with small-molecule drugs plays a key role in the combat against cancer, it still shows some limitations, e.g., severe side effects, lack of selectivity (drugs enter healthy cells or tissues, leading to undesirable systematic toxicity and low therapeutic efficacy to tumors), poor water-solubility (hampering distribution in bloodstream and leading to low bioavailability) and multidrug resistance of tumor cells (decreasing therapeutic efficacy) [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, such combined therapies for synergistic effect (the effect of two or more modalities is more than the sum of their individual effects) on tumors have emerged [ 29 , 30 , 31 ]. According to some reports, the synergistic of CHT plus PTT may eradicate in vivo tumors, largely preventing recurrence or metastasis [ 19 , 32 ]. We found that the common factor of the above successful combinational therapy is nanocarriers.…”
Section: Introductionmentioning
confidence: 99%